Age-Adjusted D-Dimer in Ruling Out Acute Aortic Syndrome. (5th February 2022) - Lee, Dayeon; Kim, Yong Won; Kim, Tae Youn; Lee, Sanghun; Do, Han Ho; Seo, Jun Seok; Lee, Jeong Hun
Abstract : Background . Recently, D-dimer has been suggested as a biomarker to rule out acute aortic syndrome (AAS). Since it increases with age, this study was conducted to reveal whether an age-adjusted D-dimer can increase diagnostic accuracy in ruling out AAS. Method . A retrospective observational study design was used. Consecutive adult patients who visited an emergency room between January 2015 and September 2020 and who underwent a D-dimer test and computed tomography angiography for suspected AAS were enrolled. We calculated the diagnostic accuracy of both the conventional (0.5  μ g/ml) and age-adjusted (age × 0.01 in patients >50 years) D-dimer cut-offs. Result . D-dimer was higher in the AAS group ( n  = 82) than in the non-AAS group ( n  = 122) (10.85 (3.61–33.12) vs. 0.40 (0.23–1.07), OR: 1.139 (CI: 1.085 – 1.195), p < 0.001 ). The D-dimer plasma level had an area under the ROC curve of 0.915 (CI: 0.873–0.956) with AAS. At the age-adjusted cutoff point compared to a 0.5  μ g/ml cutoff, the sensitivity of 97.6% and the NLR of 0.04 did not change, but the specificity increased by 5.7% to 65.6%, the PPV increased by 3.6% to 65.6%, and the NPV slightly increased by 0.2% to 97.6%. Conclusion . Compared with a conventional method, the age-adjusted D-dimer cutoff may have higher specificity and PPV while maintaining high sensitivity for ruling out AAS.